Release of promoter–proximal paused Pol II in response to histone deacetylase inhibition - Vaid, Roshan (Nucleic Acids Res, 2020)
A correlation between histone acetylation and transcription has been noted for a long time, but little is known about what step(s) in the transcription cycle is influenced by acetylation. We have examined the immediate transcriptional response to histone deacetylase (HDAC) inhibition, and find that release of promoter–proximal paused RNA polymerase II (Pol II) into elongation is stimulated, whereas initiation is not. Although histone acetylation is elevated globally by HDAC inhibition, less than 100 genes respond within 10 min. These genes are highly paused, are strongly associated with the chromatin regulators NURF and Trithorax, display a greater increase in acetylation of the first nucleosomes than other genes, and become transcriptionally activated by HDAC inhibition. Among these rapidly up-regulated genes are HDAC1 (Rpd3) and subunits of HDAC-containing co-repressor complexes, demonstrating feedback regulation upon HDAC inhibition. Our results suggest that histone acetylation stimulates transcription of paused genes by release of Pol II into elongation, and that increased acetylation is not a consequence of their enhanced expression. We propose that HDACs are major regulators of Pol II pausing and that this partly explains the presence of HDACs at active genes.